Meet Marie-Grace - Buckey, Sarah Masters, 1955- (American girls collection., 2011)
Marie-Grace Gardner, a doctor's daughter who has just returned to her native New Orleans in 1853, makes friends with Cécile Rey, whose prosperous family are free people of color, and is persuaded to change places with her at separate Mardi Gras balls.